Mini Cinema / Nor Rul Huda Nordin ... [et al.] - Nordin, Nor Rul Huda; Ahmad Noor, Noor Idayu; Abdul Razak, Nur Akashah; Mohd Noordin, Noormah; Ahmad Zaki, Nadhrah (Malaysian Entrepreneurship Development Centre (MEDEC), 2003)
Our group had discussed and decided that the most suitable location for our operation will be at the Subang Parade. We choose Subang Parade because of it is the most suitable place. The locations of the place are very strategic for the research of our project. It will ensure the success of our research because it is located at the city and near the place where entertainment mostly sought. Its physical location is also very strategic , as it connect the people from all over Subang, near the federal Highway, free from factory pollution and there seldom be any nature disaster such as flood.